Analysis of student’s mathematical problem-solving ability with moderate learning readiness based on Polya’s theory - Nur Fauziyah; Zattira Nadia Rahma (Research and Development in Education (RaDEn), 2025)
Mathematical problem-solving ability is essential to develop as it forms the foundation for critical and analytical thinking. This study aims to describe the mathematical problem-solving ability of grade XI students with moderate readiness categories based on Polya's stages: understanding the problem, devising a plan, carrying out the plan, and looking back. This research employed a qualitative descriptive method with three students from class XI-7 selected through purposive sampling. Data collection techniques included observation, written tests, and interviews. The results revealed that students in the moderate readiness category could understand and plan problem-solving well, although variations in strategies were observed, such as systematic steps, quick approaches, and personal strategies. In the stage of carrying out the plan, students generally solved problems according to their plans, albeit with minor errors due to a lack of systematic execution. In the looking back stage, most students evaluated their work, but some were less thorough in composing conclusions. This study suggests implementing problem-based learning and continuous assessment to enhance students' mathematical problem-solving abilities.